The Impact of Free Trade Zones (FTZ) on Economic Growth: A Case Study of Oecusse-Ambeno Special Administrative Region (SAR) in Timor Leste - An ShaoHong; Mohamad Dian Revindo; Nisma Anggara Samalo; William Ong (Publikasi Indonesia, 2024)
This study aims to analyse the effect of free trade zone (FTZ) on economic growth, with a case study of Timor Leste’s Special Administrative Region of Oecusse-Ambeno (RAEOA). The study employs a descriptive analysis method using secondary data and literature study. The results show that FTZs can have a positive impact on a country’s economic growth but the impact depends on various factors such as government policies, infrastructure, and political stability. In the case of Timor Leste, the RAEOA, formed in 2002 has been attracting investment and contributing to the development of key industries such as agriculture, tourism, and fisheries, as well as natural resources such as oil and gas, However, the region still faces various economic challenges such as poverty, unemployment, and lack of infrastructure. Therefore, the study suggests that Timor Leste government carefully design the spillover mechanism of FTZ to ensure that the economic growth goal is followed by the social and economic impact in a way that results in more sustainable and equitable development.